2021
DOI: 10.3390/antiox10101520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silibinin A on Bioenergetics in PC12APPsw Cells and Mitochondrial Membrane Properties in Murine Brain Mitochondria

Abstract: Introduction: Age-related multifactorial diseases, such as the neurodegenerative Alzheimer’s disease (AD), still remain a challenge to today’s society. One mechanism associated with AD and aging in general is mitochondrial dysfunction (MD). Increasing MD is suggested to trigger other pathological processes commonly associated with neurodegenerative diseases. Silibinin A (SIL) is the main bioactive compound of the Silymarin extract from the Mediterranean plant Silybum marianum (L.) (GAERTN/Compositae). It is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
2
0
1
Order By: Relevance
“…Recent studies reported that silibinin alleviated motor dysfunction in a PD mouse model by inhibiting oxidative stress, neuroinflammation, and imbalance of mitochondrial dynamics and promoting mitophagy and mitochondrial biogenesis (Liu et al, 2021b;Liu et al, 2021c). In an in vivo AD model, the silibinin intervention significantly reduced the Ca 2+ overload-induced mitochondrial swelling and improved the fluidity of the mitochondrial membrane (Esselun et al, 2021).…”
Section: Monomeric Compounds Isolated From Tcmsmentioning
confidence: 99%
“…Recent studies reported that silibinin alleviated motor dysfunction in a PD mouse model by inhibiting oxidative stress, neuroinflammation, and imbalance of mitochondrial dynamics and promoting mitophagy and mitochondrial biogenesis (Liu et al, 2021b;Liu et al, 2021c). In an in vivo AD model, the silibinin intervention significantly reduced the Ca 2+ overload-induced mitochondrial swelling and improved the fluidity of the mitochondrial membrane (Esselun et al, 2021).…”
Section: Monomeric Compounds Isolated From Tcmsmentioning
confidence: 99%
“…В качестве другого перспективного соединения можно рассмотреть флавоноид силибинин (силибин), обладающий антиоксидантной активностью [181]. Силибинин взаимодействует с митохондриальной мембраной, препятствуя дисфункции изолированных митохондрий [182] [190]. Кверцетин уменьшает дисфункцию митохондрий, снижая образование АФК, восстанавливая потенциал митохондриальной мембраны и синтез ATP; регулирует экспрессию AMP-активируемой протеинкиназы (AMPK), которая участвует в модулировании энергетического метаболизма; снижает отложение Aβ, способствует его выведению и регулирует процессинг APP [191].…”
Section: потенциальные нейропротекторные препараты воздействующие одн...unclassified
“…Another promising compound is the flavonoid silibinin (silybin), which has antioxidant activity [ 181 ]. Silibinin interacts with the mitochondrial membrane, preventing the dysfunction of isolated mitochondria [ 182 ]. Administration of silibinin decreases the MDA level and increases the activity of the antioxidant enzymes CAT, SOD, nitric oxide (NO), and glutathione (GSH) [ 183 , 184 , 185 , 186 ].…”
Section: Potential Neuroprotector Agents Acting On Both Aβ Deposition...mentioning
confidence: 99%